1989
DOI: 10.1042/bj2620469
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of inhibition by 5,6-dichloro-1-β-d-ribofuranosylbenzimidazole on calf thymus casein kinase II

Abstract: The adenosine analogue 5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB) is a specific inhibitor for RNA polymerase II transcription in vivo and in vitro [Tamm + Sehgal (1978) Adv. Virus Res. 22, 187-258; Zandomeni & Weinmann (1984) J. Biol. Chem. 259, 14804-14811]. The effect on RNA polymerase II-specific transcription seems to be mediated by its inhibition of nuclear casein kinase II [Zandomeni, Carrera-Zandomeni, Shugar & Weinmann (1986) J. Biol. Chem. 261, 3414-3419]. Inhibition studies indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
47
0

Year Published

1991
1991
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 26 publications
2
47
0
Order By: Relevance
“…DRB, a classic inhibitor of transcription, principally inhibits CDK9, the kinase component of positive transcription elongation factor b, and blocks global RNA polymerase II -dependent transcription (22,23). Additionally, DRB also inhibits other protein kinases involved in cellular metabolism such as casein kinase type II (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…DRB, a classic inhibitor of transcription, principally inhibits CDK9, the kinase component of positive transcription elongation factor b, and blocks global RNA polymerase II -dependent transcription (22,23). Additionally, DRB also inhibits other protein kinases involved in cellular metabolism such as casein kinase type II (24,25).…”
Section: Introductionmentioning
confidence: 99%
“…Neither could we show co-precipitation of CK II with ACE (data not shown). The CK II inhibitor DRB [38], however, lead to a small increase in the amount of ACE ectodomain in the medium of one cell preparation. CK II phosphorylation of ACE (Ser 1270 ) may therefore be involved in preadipocyte ACE shedding if these preliminary data were to be confirmed.…”
Section: Discussionmentioning
confidence: 99%
“…Among these are multiple kinase inhibitors, such as sorafenib and gefitinib (Johnstone et al, 2008). Unlike DRB and some of its derivatives, many of these inhibitors have been shown to be of rather modest target selectivity (Karaman et al, 2008;Meggio et al, 1990;Zandomeni and Weinmann, 1984). It is therefore conceivable that synergies observed in TRAIL co-treatments could in part be mediated by impaired CK2 activity or Bid phosphorylation.…”
Section: The Lag Time Between Caspase-8 and Bid Activation Is Sensitimentioning
confidence: 99%
“…To achieve rapid and specific CK2 inhibition in all cells observed, we employed a short (2 hour) pretreatment with the specific CK2 inhibitor 5,6-dichloro-l-(-D-ribofuranosyl-1)-benzimidazole (DRB) (Meggio et al, 1990;Zandomeni and Weinmann, 1984). Time-lapse imaging of control HeLa cells, as expected, showed that the IETD FRET probe was cleaved before tBid-Cherry translocation could be detected (Fig.…”
Section: The Lag Time Between Caspase-8 and Bid Activation Is Sensitimentioning
confidence: 99%